Rabies virus in a pregnant naturally infected southern yellow bat (Lasiurus ega) - SD Allendorf; A Albas; JRB Cipriano; JMAP Antunes; CM Appolinário; MG Peres; AR da Rosa; MM Sodré; J Megid (Journal of Venomous Animals and Toxins including Tropical Diseases, 2011)
Current knowledge on bat lyssavirus infections in their native hosts is limited and little is known about the virulence, virus dissemination and transmission among free-living insectivorous bats. The present study is a brief description of rabies virus (RABV) dissemination in tissues of a naturally infected pregnant southern yellow bat (Lasiurus ega) and its fetuses, obtained by reverse-transcriptase polymerase chain reaction (RT-PCR). The RT-PCR was positive in samples from the brain, salivary gland, tongue, lungs, heart, kidneys and liver. On the other hand, the placenta, three fetuses, spleen, intestine and brown fat tissue tested negative. This research demonstrated the absence of rabies virus in the fetuses, thus, in this specific case, the transplacentary transmission was not observed.